Business and service telephone conversations an investigation of British English, German and Italian Encounters - Varcasia, Cecilia; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book considers the sequential deployment of the receiver's response to the caller's request in telephone service encounters between native speakers in the U.K, Germany and Italy analysing the different response formats and their grammatical configuration.
Keywords: Linguistics; Literature -- Translations; Sociolinguistics; Discourse analysis; Communication; Linguistics; Sociolinguistics; Communication Studies; Translation Studies; Discourse Analysis